Evidence for a new structure in the J/ψp and J/ψp̄ systems in B0s→J/ψpp̄ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2022)
An amplitude analysis of flavor-untagged B0s→J/ψpp̄ decays is performed using a sample of 797±31 decays reconstructed with the LHCb detector. The data, collected in proton-proton collisions between 2011 and 2018, correspond to an integrated luminosity of 9 fb−1. Evidence for a new structure in the J/ψp and J/ψ¯p systems with a mass of 4337+7−4 +2−2 MeV and a width of 29+26−12 +14−14 MeV is found, where the first uncertainty is statistical and the second systematic, with a significance in the range of 3.1 to 3.7σ, depending on the assigned JP hypothesis.